An Analysis of Readiness Factors of GOES (Guide Objective Eementary School) Mobile Learning in Elementary School - Hilaliyah, Hilda; Novianti, Desi; Anjani, Dewi (International Journal of Engineering and Technology, 2018)
This study proposes a determination of readiness factors in elementary school to accept the application of GOES mobile learning in the process of Teaching and Learning Activities. The other is to find out what factors are considered sufficient to help the implementations. This research is descriptive research whom using a questionnaire media based on Aydin & Tasci's e-learning readiness (ELR) model with a rating scale. This questionnaire consists of 25 questions and will be grouped into four factors. These factors are technological factors, innovation factors, human resources factors, and self-development factors. The type of data in this study is the quantitative type. The study locations were in Elementary School of 15, 19, 20, 21, and 22 in DKI Jakarta with only 75 questionnaires from 180 questionnaires distributed. The results of the questionnaire for Elementary School of 15 showed an ELR score of 4.04 which means the school is ready to implement e-learning, while for Elementary School of 19 showed an ELR score of 3.89, Elementary School of 20 showed an ELR score of 3.91, Elementary School of 21 showed an ELR score of 3.86 and Elementary School of 22 showed an ELR score of 3.83 which means in the ready category but needs a few improvement..Â Â